HBIM: Vernacular Architecture Study of Uma Kabuong Limo with Paranginan Roof Type - Muhd. Arief Al Husaini; Wahyu Hidayat; Mashuri; Indra Kuswoyo (International Journal of Architecture and Urbanism, 2026)
Kampung Pulau Belimbing is a traditional village in Limo Koto that is currently included in the administrative area of the Kampar Regency. One of the uniqueness is depicted in the Uma Kabuong Limo building which is found in various forms. One of the exclusive varieties is Uma Kabuong Limo with a multi-storey roof type. The development of this type was influenced by Malay architecture in Malaysia because the owner of this house worked for a long time in the country Malaysia. This study aims to document the vernacular architectural typology of the Uma Kabuong Limo multi-storey roof type. This research approach is descriptive and qualitative with a combination of synchronic analysis and diachronic reading. Modeling and simulation research reproducing reality through substitute media. Furthermore, the data obtained through observation and interviews are used for model creation as a simulation tool. The creation of this model is through a heritage building information modeling (HBIM) approach. HBIM is a process of informing in the form of simulations similar to cultural heritage buildings to facilitate decision-making in the management of cultural heritage buildings. In this study, a study of the architectural typology of Uma Kabuong Limo's multi-storey roofs was obtained. This building has a multi-storey roof development called a paranginan roof. The existence of carvings, the manufacture of fine buildings, and selected wood materials indicate the high social and economic status of the owner in the people of Kampung Pulau Belimbing.